2010
DOI: 10.1111/j.1600-0706.2010.18519.x
|View full text |Cite
|
Sign up to set email alerts
|

Insect biological control accelerates leaf litter decomposition and alters short‐term nutrient dynamics in aTamarix‐invaded riparian ecosystem

Abstract: Insect herbivory can strongly influence ecosystem nutrient dynamics, yet the indirect effects of herbivore‐altered litter quality on subsequent decomposition remain poorly understood. The northern tamarisk beetle Diorhabda carinulata was released across several western states as a biological control agent to reduce the extent of the invasive tree Tamarix spp. in highly‐valued riparian ecosystems; however, very little is currently known about the effects of this biocontrol effort on ecosystem nutrient cycling. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 53 publications
1
14
1
Order By: Relevance
“…, Frost , Uselmann et al . ), but not in a dry environment, where frass stayed undecomposed on the soil surface (Hunter ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Frost , Uselmann et al . ), but not in a dry environment, where frass stayed undecomposed on the soil surface (Hunter ).…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the amounts of N returned to soil in litter and frass, soils had similar N values (for N, hypothesis 2 did not hold). Elsewhere, lepidopteran outbreaks have resulted in an increase in soil N content in wet environments (Fogal & Slansky 1985, Hollinger 1986, Chapman et al 2003, Frost 2005, Uselmann et al 2011, but not in a dry environment, where frass stayed undecomposed on the soil surface (Hunter 2001).…”
Section: Discussionmentioning
confidence: 99%
“…A greenhouse experiment determined that beetle herbivory damages leaf and stem tissues and produces transient upward spikes in water loss both during the day and nighttime due to wounding and uncontrolled water loss (Snyder, Uselman, Jones, & Duke, 2010). After herbivory, significant beetle damage causes the leaves to desiccate and prematurely senesce (Uselman, Snyder, & Blank, 2011). The net effect on ET will depend on the intensity of beetle defoliation and the ability of tamarisk to regrow leaves.…”
Section: Introductionmentioning
confidence: 99%
“…However, the present study found no evidence of such a positive relationship, and even showed a negative relationship between palatability and decomposability. However, the plant responses to insect herbivory would be an important factor in determining the relationship between palatability and decomposability through changes in the litter decomposition process (Findlay et al, 1996;Uselman et al, 2011). These findings indicate that L. dispar larvae may accelerate the decomposition process in temperate deciduous forests through selective feeding on plants with relatively low litter decomposability and producing frass with higher decomposability than the litter.…”
Section: Ecosystem Consequences Of Herbivore Selective Feedingmentioning
confidence: 98%